How are informed consents obtained in the Philippine General Hospital - Chaves, Florence May.; Dancel, Maricel; Irasusta, Michiko; Quioyo, Guillermina; Rullado, Cristeta; Tanhueco, Vivian; Tolentino, Cheryl Liz. (Manila College of Nursing University of the Philippines Manila, 1994)
The process of coming up with & research Paper on informed consent was surely an interesting yet physically and mentally taxing new task for the Whole group. We had to start with coming up with the brightest idea for our topic and then proceed with the process of gathering our sources, developing a methodology and sampling scheme, identifying Problems, proving/disproving hypotheses and finally coming up with conclusions, implications and recommendations. The question posed by the group: “How are informed consent obtained in the Philippine General Hospital?” is both a product of our curiosity and our drive to effect a change or an improvement in the system if found necessary. Our constant and continuous clinical experience in the ward has exposed us to various SOP’s of which some are essential while others are useless and negligible, But the whole group realized the significance of the often neglected hospital form and thought it necessary to validate/confirm this idea. Thus, an opportunity to apply all the nursing principles and ideas learned from Nursing Research/N-199 was brought forth through the query.
Research (In partial fulfillment of the requirements in the course N199: Nursing Research) -- University of the Philippines Manila, April 1994.
Keywords: Nursing -- Research